Sarī jatī retī - Mahetā, Yaśodhara (Gūrjara Grantharatna Kāryālaya, 1995)
Stories on social condition of women in men dominated society
Short stories. - Reprint. Originally published: 1950. - In Gujarati-Schr
Keywords: Short stories; Gujarati